Case Report: Analysis of Inflammatory Cytokines IL-6, CCL2/MCP1, CCL5/RANTES, CXCL9/MIG, and CXCL10/IP10 in a Cystic Fibrosis Patient Cohort During the First Wave of the COVID-19 Pandemic - Baresi, Giulia; Giacomelli, Mauro; Moratto, Daniele; Chiarini, Marco; Conforti, Immacolata Claudia; Padoan, Rita; Poli, Piercarlo; Timpano, Silviana; Caldarale, Francesca; Badolato, Raffaele (Frontiers in Pediatrics, 2021)
Since the beginning of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, data registered in the European countries revealed increasing cases of infection in cystic fibrosis (CF) patients. In the course of this pandemic, we enrolled 17 CF patients for a study evaluating inflammatory markers. One of them developed COVID-19, giving us the possibility to analyze inflammatory markers in the acute phase as compared to levels detected before and after the infectious episode and to levels measured in the other CF patients enrolled to the study who did not experience COVID-19 and 23 patients referred to our center for SARS-CoV-2 infection.